2005
DOI: 10.3354/meps304265
|View full text |Cite
|
Sign up to set email alerts
|

Fate of copepod faecal pellets and the role of Oithona spp.

Abstract: Because the downward flux of zooplankton faecal pellets (FP) measured in sediment traps is typically lower than FP production in overlaying waters, it is inferred that FP are recycled. One suggested explanation for low export fluxes of FP is retention through processes such as FP ingestion (coprophagy) and FP fragmentation (coprorhexy). It has become accepted that the globally important cyclopoid copepod Oithona spp. are one of the main organisms causing high retention of copepod FP, however, the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 37 publications
1
35
0
1
Order By: Relevance
“…This calculation gives potential ingestion rates of 147, 87 and 177 mg C m -2 d -1 by the migrating zooplankton population in the upper water column on Days 2, 4 and 6, respectively. These ingestion rates could have been underestimated due to potential coprophagy/coprorhexy by the ubiquitous small calanoid copepod Oithona similis (Reigstad et al 2005) which was the most abundant zooplankton species in the upper 100 m of the water column throughout the study period (E. Head, Bedford Institute of Oceanography, pers. comm.).…”
Section: Mesozooplankton Grazing In the Upper Twilight Zonementioning
confidence: 99%
“…This calculation gives potential ingestion rates of 147, 87 and 177 mg C m -2 d -1 by the migrating zooplankton population in the upper water column on Days 2, 4 and 6, respectively. These ingestion rates could have been underestimated due to potential coprophagy/coprorhexy by the ubiquitous small calanoid copepod Oithona similis (Reigstad et al 2005) which was the most abundant zooplankton species in the upper 100 m of the water column throughout the study period (E. Head, Bedford Institute of Oceanography, pers. comm.).…”
Section: Mesozooplankton Grazing In the Upper Twilight Zonementioning
confidence: 99%
“…Vials were placed in the dark in a submerged plankton wheel at 17°C rotating at 1 rpm to keep the material in suspension (see e.g. Reigstad et al 2005). Oxygen was monitored every 6 to 8 h for 48 h with an oxygen sensor microsensor (Unisense AS) and never dropped below 15 to 20% (Renaud et al 2007).…”
Section: Faecal Pellet Carbon Demand Through Microbial Respirationmentioning
confidence: 99%
“…While cyclopoid copepods of the genus Oithona have for some time been considered the main grazers on FP (González & Smetacek 1994, Svensen & Nejstgaard 2003, more recent studies suggest that this is not always the case and that other flux-feeding organisms must also be taken into consideration (Reigstad et al 2005, Iversen & Poulsen 2007. For instance, protozooplankton are able to use FP as a direct food source (Jacobsen & Azam 1984, Noji 1991, Turner 2002, Poulsen & Kiørboe 2006, Poulsen & Iversen 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lampitt & Gamble 1982;Drits & Semenova 1984;Uchima & Hirano 1986). Oithonids have also been observed to feed on fecal pellets of other zooplankton (González & Smetacek 1994), though their coprophagous feeding is still controversial (Reigstad et al 2005;Iversen & Poulsen 2007). Recent experimental studies employing natural prey assemblages have revealed that oithonids feed selectively on microzooplanktonic protists, such as ciliates and heterotrophic dinoflagellates (e.g.…”
mentioning
confidence: 99%